Pengaruh Karton Telur dalam Mengembangkan Kreativitas Anak di Taman Kanak-kanak Islam Silaturahmi Kecamatan V Koto Kampung Dalam Kabupaten Padang Pariaman - Faradilla, Keysa; Anggraini, ViVi (Lembaga Yasin AlSys, 2023)
This study is motivated by the lack of development of children's creativity abilities caused by the use of media, methods and learning approaches that are less varied so that the purpose of this study is to determine the effect of egg cartons in developing children's creativity in the Silaturahmi Islamic Kindergarten, V Koto Kampung Dalam District, Padang Pariaman Regency. This study uses quantitative research in the form of quasi-experimental with the type of nonequivalentcontrol grub design which aims to determine the independent variable of the remaining material of egg cartons on the dependent variable of children's creativity after use. Data collection techniques and used oral tests and action tests, in the form of statements as many as 6 items and this data analysis technique uses normality test, homogeneity test and hypothesis test SPSS 26 for windows. the results showed that the data was normally distributed and homogeneous. Furthermore, based on the t test, it is known (2-tailed) is 0.01 <0.05 so it can be concluded that egg carton media has an effect in developing children's creativity at the Silaturahmi Islamic Kindergarten, V Koto Kampung Dalam District, Padang Pariaman Regency.